PENGARUH IKLAN DAN CITRA MEREK TERHADAP MINAT BELI KONSUMEN PRODUK MEREK HONDA (Survei Konsumen Pada Dealer CV. Cempaka Motor di Kabupaten Sijunjung) - Saputra, Randi; Karneli, Okta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to find out how the influence of advertising (advertising messages, advertising copy, advertising design, advertising model, color and music advertising) and brand image (brand association superiority, brand association strength and uniqueness of brand association) to consumer buying interest , favorite, choice, confidence and purchase) Honda brand products at dealers CV. Cempaka Motor in Sijunjung District. The population in this study were consumers who bought Honda brand motorcycles at dealers CV. Cempaka Motor in Sijunjung District. Sampling in this research that is amounted 93 sample using slovin formula. The data collection of this research is primary data with dissemination of research instrument and secondary data in the form of company archives, data analysis in this research using multiple regression, partial test (t test), test of determination (r test) and simultaneous test (f test) with SPSS program help . The results showed that the variables of advertising and brand image partially (t test) significantly influence consumer buying interest in Honda brand products on the CV. Cempaka Motor in Sijunjung District. Results simultaneously (f test) showed a significant influence of advertising variables and brand image on consumer buying interest in Honda brand products on CV. Cempaka Motor in Sijunjung District. Keywords : Advertisement, Brand Image, Consumer Buying Interest